A Comprehensive Review On Pharmacological Activity Of Terminalia Catappa (Combretaceae)- An Update - Mallik, Jony; Al, Faruq Abdullah; Kumar, Banik Rony (Asian Journal of Pharmaceutical Research and Development, 2018)
The main aim of this review is to make a proper profile of about the pharmacological activity of Terminalia catappa ( Combretaceae). Terminalia catappa is a very useful medicinal plants that are growing at the different districts of Bangladesh. The local or bangla name of Terminalia catappa is Bangla Badam. English name are Country Almond, Indian Almond. Terminalia catappa is native to the Indian Ocean island of Madagascar. The distinct part this plant may possess different pharmacological activity to the human being. The plant contains Gallic acid, allagic acid, corilagin and unidentified flavonoids have been isolated from leaves, fruits and bark. Oil from fruits resembled almond oil. The present article attempts to provide comprehensive information on pharmacological properties of Terminalia catappa for further potential research.